RISKS AND PROBLEMS OF THE BANKING SYSTEM IN 2015 - P. Fedorova; O. Solntseva (Вестник университета)
Existing risks in 2015 are considered. A comparative risk analysis 2008-2009 and 2015 is presented. Causes of the problems of the banking system are allocated. The evaluation of public policies impact on the stability of banks is given. The ways out of the banking system from the crisis are proposed.